مبادئ وأسس الوظيفة العامة في الجزائر - عزيز حسين, العيد (University of Eloued جامعة الوادي, 2023)
In the midst of our study of the subject of the principles and foundations of the public office in Algeria, the first chapter was presented in this study as a theoretical framework, in which we dealt with the conceptual determinants of the public office. As well as employment and the public employee from the concept of human resources management, then the definition of the public employee from a jurisprudential as well as legislative standpoint, and the nature of the relationship that binds him to the department used As for the second chapter, as an applied framework, we have studied the consecration of the principles and foundations of the public service in Algeria, by reforming the position according to the principles based on it, and activating the performance of the public employee through the consecration of the closed system, and the position of the Algerian legislator on it and the reasons for its adoption, and this is what was evident to us in Order 03/06 related to The Basic Law of the Public Service, which led to the conclusion of the consecration of constitutional principles such as the principle of separation of powers and the recognition of the privacy of the public service sector from the private sector and its inclusion of the rights and guarantees of the public employee exercised in his capacity as a citizen in addition to referring to the bodies of participation and dialogue, especially the Supreme Council of the Public Service. All of this did not reach Order 03/06 and the regulatory texts applied to it to the desired reform, so it is necessary to reconsider the system of public employment, even in a relative way, in order to bring about a deeper reform. في خضم دراستنا لموضوع مبادئ وأسس الوظيفة العمومية في الجزائر تم التعرض في هذه الدراسة للفصل الأول كإطار نظري ، تناولنا فيه المحددات المفاهيمية للوظيفة العامة وكذا التوظيف والموظف العام من مفهوم إدارة الموارد البشرية, ثم التعريف بالموظف العام من منطلق فقهي وكذا تشريعي، وطبيعة العلاقة التي تربطه بالإدارة المستخدمة أما الفصل الثاني كإطار تطبيقي، قمنا بدراسة تكريس مبادئ وأسس الوظيفة العمومية في الجزائر ، بإصلاح الوظيفة وفق المبادئ القائمة عليها ، وتفعيل أداء الموظف العمومي من خلال تكريس النظام المغلق، وموقف المشرع الجزائري منه وأسباب الأخذ به وهذا ما تجلى لنا في الأمر 03/06 المتعلق بالقانون الأساسي للوظيفة العمومية, مما أدى إلى الوصول لنتيجة مفادها تكريس المبادئ الدستورية كمبدأ الفصل بين السلطات والاعتراف بخصوصية قطاع الوظيفة العمومية عن القطاع الخاص وتضمينه لحقوق وضمانات الموظف العمومي يمارسها بصفته مواطنا بالإضافة للرجوع إلى هيئات المشاركة والحوار ، لاسيما المجلس الأعلى للوظيفة العمومية إلى أنه وبالرغم من كل هذا لم يصل الأمر 03/06 والنصوص التنظيمية المطبقة له إلى الإصلاح المرجو ، لذالك لابد من إعادة النظر في نظام الوظيفة العمومية ولو بشكل نسبي من أجل إحداث إصلاح أعمق
مذكرة ماستر
Keywords: : public office ** public service law ** employee performance; الوظيفة العامة ** قانون الوظيف العمومي ** اداء الموظف